Wasp Parasitoid Meteorus autographae Muesebeck (Insecta: Hymenoptera: Braconidae) - Andrei Sourakov; Everett Mitchell (EDIS, 2002)
This document is EENY-125, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2000. Revised: October 2002.